Syria Neoliberal Reforms in Health Sector Financing: Embedding Unequal Access? - Kasturi Sen; Waleed al Faisal (Social Medicine Publication Group, 2012)
The recent volatility and uprisings in several countries of the Arab world have been interpreted by the West solely as a popular demand for political voice. However, in all the countries of the region, including those in which there is ongoing violent opposition, the underlying economic dysfunction speaks for itself. The legacy of joblessness, food riots, and hunger is commonplace and is most often related to structural reforms and austerity measures promoted by the IMF and World Bank. These have played a significant role in reinforcing the rich-poor divide over the past three decades, fostering inequality, suffering, social divisions, and discontent, which are often overlooked by Western observers. In Syria, the state introduced policies for the liberalization of the economy as early as 2000; these were formalized into the 10th Five-Year Plan (2006-2010). Economic liberalization has been supported by the European Union with technical support from the German Technical Cooperation agency (GTZ). Changes made to the health sector and the labor market include: the piloting of health insurance schemes to replace universal coverage, the charging of fees for health services in public hospitals, and job losses across the board. While the West views discontent in Syria largely as political, its own role in promoting economic reforms and social hardship has been largely missed. In large part, discontent in Syria and in the region as a whole are a part of a phenomenon that has repeatedly highlighted the failure of policies that aim at rapid commercialization with little consideration for pre-existing disparities in wealth and resources. This paper traces some of the proposed changes to the financing of health care and examines the implications for access and equity. re and examines teh implications for access and equity.